Development of a robust and efficient biogas processor for hydrogen production. Part 2: Experimental campaign. (4th January 2018) - Montenegro Camacho, Y.S.; Bensaid, S.; Lorentzou, S.; Vlachos, N.; Pantoleontos, G.; Konstandopoulos, A.; Luneau, M.; Meunier, F.C.; Guilhaume, N.; Schuurman, Y.; Werzner, E.; Herrmann, A.; et al.
Abstract: In this study, a robust and efficient decentralized fuel processor based on the direct autothermal reforming (ATR) of biogas with a nominal production rate of 50 Nm 3 /h of hydrogen and a plant efficiency of about 65% was developed and tested. The ATR unit is composed of a structured catalyst support for the biogas reforming close coupled to a catalytic wall-flow filter to retain eventual soot particles. The performance of the conventional random foam and homogeneous lattice supports structures for the production of hydrogen from the ATR reaction was investigated. 15–0.05 wt%-Ni-Rh/MgAl2 O4 -SiSiC structured catalyst and LiFeO2 -SiC monolith were selected for the conversion of biogas to hydrogen and for the syngas post-treatment process, respectively. For all the experiments, a model synthetic biogas was used and the catalytic activities were evaluated in three different experimental facilities: lab bench, pilot test rig and demonstration plant. High methane conversions (>95%) and hydrogen yields (>1.8) reached in the lab bench were also achieved in the pilot and demonstration plant operating at different GHSV. Results of duration test using a foam coupled to the filter has demonstrated that the pre-commercial processor is reliable while offering a satisfactory reproducibility and negligible pressure drop. A thermodynamic equilibrium and a cold gas efficiency of 90% were reached for an inlet temperature of 500 °C, O/C: 1.1 and S/C: 2.0, as predicted with the Aspen simulation. Highlights: Fuel processor development and testing for hydrogen production based on the direct ATR of biogas. SiSiC structured catalyst for the conversion of biogas to hydrogen. 15–0.05 wt% Ni-Rh/MgAl2 O4 is a robust catalyst for the ATR of biogas. LiFeO2 is the most prominent catalyst carbon gasification in a reducing atmosphere. The fuel processor is reliable and offers a satisfactory reproducibility.